Efektivitas Konseling Laktasi dalam Meningkatkan Kepercayaan Diri Ibu Menyusui - Ishmatika, Enka Nur (Barongko: Jurnal Ilmu Kesehatan, 2025)
Breastfeeding mothers' self-confidence significantly influences the success of exclusive breastfeeding and the continuation of breastfeeding. Lactation counseling is an intervention that can improve mothers' knowledge, skills, and confidence in breastfeeding. This study aims to analyze the effectiveness of lactation counseling in improving breastfeeding mothers' self-confidence. The research method used a quasi-experimental pre-test and post-test with a control group. The sample consisted of 60 breastfeeding mothers at Community Health Center X, divided into an intervention group (n=30) who received lactation counseling and a control group (n=30) who received routine services. Self-efficacy was measured using the Breastfeeding Self-Efficacy Scale (BSES) before and after the intervention. Data were analyzed using paired t-tests and independent t-tests. The results showed a significant increase in maternal breastfeeding confidence in the intervention group (mean pre-test 52.4 → post-test 78.6, p<0.001) compared to the control group (mean pre-test 53.1 → post-test 56.8, p>0.05). These findings confirm that lactation counseling is effective in increasing maternal breastfeeding confidence.